2005
DOI: 10.1177/0885066605279068
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Pulmonary Failure Attributable to Viral Pneumonia With Human Herpes Virus 6 (HHV6) in a Young Immunocompetent Woman

Abstract: Adult respiratory distress syndrome (ARDS) attributable to viral pneumonia is described mainly in immunodeficient persons. ARDS caused by human herpes virus 6 (HHV6) is extremely rare, and to our knowledge only 1 case has been reported in the literature. We present the case of a young woman who developed fatal pulmonary failure most probably attributable to HHV6 pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 4 publications
3
11
0
2
Order By: Relevance
“…The radiological findings were described only as progressive bilateral interstitial infiltrates on chest radiographs. Meanwhile, Merk et al [9] reported fatal pulmonary failure in a healthy 19-year-old woman. The chest radiographs showed developing pulmonary infiltration at the basal region of both lungs, with large amounts of pulmonary effusions; however, no previous reports have published CT images.…”
Section: Discussionmentioning
confidence: 99%
“…The radiological findings were described only as progressive bilateral interstitial infiltrates on chest radiographs. Meanwhile, Merk et al [9] reported fatal pulmonary failure in a healthy 19-year-old woman. The chest radiographs showed developing pulmonary infiltration at the basal region of both lungs, with large amounts of pulmonary effusions; however, no previous reports have published CT images.…”
Section: Discussionmentioning
confidence: 99%
“…Herpes simplex virus, cytomegalovirus, varicella-zoster virus, Epstein-Barr virus, human herpesvirus 6, and Kaposi's sarcoma-associated herpesvirus (KSHV) have all been associated with respiratory diseases (7,10,30,33,42,46). Much of our understanding of immune responses to viral infection of the respiratory tract comes from experimental animal models.…”
mentioning
confidence: 99%
“…Los microorganismos que se han asociado a hipoxemia severa y progresión a SDRA son el virus sincicial respiratorio, el infl uenza A H1N1 pandémica, Pneumocystis jirovecii, VHS-1, virus del herpes simplex tipo 6, virus de Epstein Barr, virus infl uenza A H5N1, Chlamydia pneumoniae y metaneumovirus humano, entre otros [16][17][18][19] . El diagnóstico de trabajo del caso reportado, fue una neumonía grave con hipoxemia severa y progresión a SDRA; aunque los estudios microbiológicos y serológicos fueron negativos para detectar el agente etiológico, la prescripción de los antibióticos empíricos obedeció probablemente a la rápida progresión y severidad del cuadro clínico, la no detección del agente etiológico y la pobre respuesta, en las primeras 24 a 48 horas, de los tratamientos instaurados.…”
Section: Discussionunclassified